Similarity of Chlamydia pneumoniae strains in the variable domain IV region of the major outer membrane protein gene. - Gaydos, C A (1992)
DNA was amplified by polymerase chain reaction from the gene encoding the major outer membrane protein (MOMP) of Chlamydia pneumoniae in order to examine the relatedness of strains isolated from diverse geographical regions. Primers for this reaction were chosen to span a 207-bp region comparable to that of the fourth variable segment of the MOMP gene of Chlamydia trachomatis. Among C. trachomatis, sequence heterogeneity is characteristic within variable sequence domain IV (VDIV) and correlates with serovar type. In contrast, sequence analysis of polymerase chain reaction products from 13 C. pneumoniae isolates indicated that all tested strains were identical in this segment of the MOMP gene. The predicted amino acid sequences from the C. pneumoniae VDIV gene products shared only 13.3 to 30% homology with published VDIV regions from serovars of C. trachomatis. Homology of these VDIV amino acid sequences with sequences from strains of C. psittaci ranged from 45.7 to 60%. The sequence conservation of the VDIV region of the MOMP gene indicates that C. pneumoniae strains may be more genetically homogeneous than C. trachomatis or Chlamydia psittaci strains. Future investigations of antigenic diversity among C. pneumoniae strains should be aimed at the evaluation of variation in other regions of the C. pneumoniae genome.